The Effect of Accounting Information Systems and Online Shopping on Impulsive Buying on Shopee E-Commerce Users - Sarah Aulia Safitri; Nunung Aini Rahmah (Social Science Studies, 2023)
The Accounting Information System on Shopee e-commerce is transparent to give its customers access to some of these accounting systems, one of which is that consumers can place orders and even see the availability of goods in a store. Online shopping can also make buying and selling activities easy and flexible, which can be reached and accessed whenever consumers want. This study aimed to determine and analyze the influence of Accounting Information Systems and Online Shopping on Impulsive Buying in E-Commerce Shopee Case Studies on Students of the Faculty of Economics and Business, Jenderal Achmad Yani University. The population in this study was 2,231student the Faculty of Economics and Business and 100 as a sample by distributing questionnaires. This research is quantitative research with a nonprobability sampling technique using purposive sampling. This research uses variable free, namely Accounting Information Systems and Online Shopping, and variable bound, namely Impulsive Buying. The results showed that the Accounting Information System had a positive and significant effect on Impulsive Buying, and Online Shopping had a positive and significant effect on Impulsive Buying.